Character Education Base on Local Wisdom in Aceh (Study on Tradition of Children Education in Aceh Community) - Samad, Sri Astuti A. (Al-Ulum, 2015)
This study explains about education of children character which base on local wisdoms in Aceh community. The study used historical, sociological and anthropological approach. The local wisdoms have dealt with Islamic religion which is strongly practiced by Aceh community. Religion and Aceh local wisdoms have become part of Aceh community identity for a long time. In this regard, it can be seen in hadih majah (quotes of Aceh): âhukom ngon adat lagee zat ngon sifeutâ, it means that religion and tradition are like substance and attribute that cannot be separated. Children education in Acehnese tradition has several phases namely: azan and iqamah, boh nan (naming of child), peutron aneuk (bringing of child into the ground), aqÄ«qah (sacrificing of goat for new-born baby), doda idi (singing and telling story to the child), euntat beut (bringing of child to Islamic school to recitate the holy Quran), peutamat beut (make special party for children after their finishing recitating of the holy Quran). The result of this study shows that those traditions were very important identities to the children of Aceh particularly to perform a good characters and personalities. It also can grow values of tauhid, kindness, togetherness, and intelligence.-----Kajian ini menjelaskan tentang pendidikan karakter anak yang berbasis kearifan lokal dalam Masyarakat Aceh. Studi ini menggunakan pendekatan historis, sosiologis dan antropologis. Kearifan lokal tersebut memiliki kaitan yang erat dengan agama Islam yang dianut secara kuat oleh masyarakat Aceh. Hal ini terlihat dalam hadih majah (pepatah): âhukom ngon adat lagee zat ngon sifeutâ, artinya hukum [agama] dan adat, seperti zat dengan sifatnya, tidak dapat dipisahkan. Tradisi mendidik anak dalam masyarakat Aceh dapat disebutkan fase-fasenya yaitu; azan dan iqamah, boh nan (memberi nama), peutron aneuk (bayi diturunkan ke tanah), aqÄ«qah, doda idi (bernyanyi atau bercerita), euntat beut (mengantar mengaji), peutamat beut (tamat mengaji). Temuan penelitian ini menunjukkan bahwa tradisi tersebut merupakan entitas yang cukup penting bagi anak dalam memperoleh pendidikan karakter sehingga tertanam nilai-nilai; ketauhidan, kebaikan, kebersamaan, kepahlawanan dan kecerdasan.